Development Of The Word Snake And Ladder Media In Improving Early Reading Skills For Preschool Children In Group B - Cahyati, Deti; Yolanda Pahrul; Maulida Nur; Mutoharoh Mutoharoh; Galuh Mulyawan (UNIB Press, 2026)
Early reading skills are crucial for young children, although in practice, many children still have difficulty identifying letters and words. This study developed the Ular Tangga Kata (URGATA) media through the Research and Development (R&D) method using the ADDIE model. The validation test results showed that this media is suitable for use, with a score of 80% from media experts and 77.1% from subject matter experts, as well as receiving excellent appreciation (92%) from education practitioners. Empirically, the use of URGATA has been proven effective in improving children's reading skills, as seen from the increase in the average score from 44 to 84 with an N-Gain value of 0.7 (moderate category). Therefore, URGATA is an effective learning media solution to stimulate early reading skills